Regional economic growth in China from a Kaldorian perspective: A comparative study of Nanjing and Suzhou - Alexandre Gomes (PSL Quarterly Review, 2020)
This paper sets out to analyse and compare the growth performances of two Chinese cities, Nanjing and Suzhou. Their growth performances have varied over time, with one city outperforming the other in some periods, and with the reverse scenario taking place in other times. In order to explain this phenomenon, this study makes use of a Kaldorian analytical framework, highlighting key notions such as demand-led growth, path-dependency, lock-in effects and inter-relatedness. It will be argued that regional economic growth is explained by the match - or otherwise - between a city's productive structure and China's national aggregate demand composition.
Keywords: P25; R11; N95; 330; Regional economic growth; Kaldor; Nanjing; Suzhou; Regionales Wachstum; Postkeynesianische Wachstumstheorie; China